ANALYSIS OF SIPD IMPLEMENTATION AT THE REGIONAL FINANCIAL AND ASSET MANAGEMENT AGENCY (BPKAD) OF CIMAHI CITY BASED ON HOME AFFAIRS MINISTERIAL REGULATION NO. 70 OF 2019 - Utami, Melydian Nur; Afriady, Arif (Accounting Department, Politeknik Negeri Bandung, 2025)
This study aims to find out how the implementation of SIPD in BPKAD Cimahi City in 2024 is seen from the information system components in the form of software, hardware, procedures, databases, communication networks, and users that have an impact on the realization of transparency and accountability. This study uses a qualitative method with the type of case study research, types and sources of data obtained from SIPD users as the main informant at BPKAD Cimahi City, the data collection techniques used are interviews, observations, and documentation, data validity tests are carried out by triangulation techniques and source triangulation, and data analysis consists of data reduction, data presentation, conclusions drawn, and research recommendations with the help of the NVivo 12 Pro application. The results of the study were obtained that the implementation of SIPD at BPKAD Cimahi City in 2024 has met several components of the information system such as the availability of hardware, communication networks, the suitability of implementation with procedures, and the availability of recovery functions in the database. However, it still needs to be developed on software components and user understanding. Nevertheless, it still realizes increased transparency and accountability.